A Study of the Effect of Molecular and Aerosol Conditions in the Atmosphere on Air Fluorescence Measurements at the Pierre Auger Observatory - Collaboration, TPA (2010)
The air fluorescence detector of the Pierre Auger Observatory is designed to perform calorimetric measurements of extensive air showers created by cosmic rays of above 10^18 eV. To correct these measurements for the effects introduced by atmospheric fluctuations, the Observatory contains a group of monitoring instruments to record atmospheric conditions across the detector site, an area exceeding 3,000 km^2. The atmospheric data are used extensively in the reconstruction of air showers, and are particularly important for the correct determination of shower energies and the depths of shower maxima. This paper contains a summary of the molecular and aerosol conditions measured at the Pierre Auger Observatory since the start of regular operations in 2004, and includes a discussion of the impact of these measurements on air shower reconstructions. Between 10^18 and 10^20 eV, the systematic uncertainties due to all atmospheric effects increase from 4% to 8% in measurements of shower energy, and 4 g/cm^2 to 8 g/cm^2 in measurements of the shower maximum.